Analysis of Psychomotor Domain Objectives from the Perspective of Educational Theorists - Nasrudin, Ega; Anwar, Saepul; Roslan Abdur Rahman (Mitra Edukasi dan Publikasi, 2025)
Achieving a number of skills is the goal of education in the 21st century. To achieve these skills, an understanding of the psychomotor aspects is required. Understanding the psychomotor aspects can help teachers or instructors to measure the extent to which individuals have achieved the desired skills. This research aims to explore the concept of psychomotor taxonomy from various educational figures. The method used in this research is the literature study method. Primary data was obtained from various scopus-indexed journal literature. While secondary data sources are obtained from other relevant journals, the data is then analyzed according to the content analysis stage. The conclusion of this research found that psychomotor taxonomy has an important role in learning, especially in developing and measuring aspects of skills. Each educational figure offers different views and stages, ranging from imitation to creation (Dave), specific response to rule use (Buttler), and reflex movement to non-discursive communication (Mardapi). Overall, this study provides insights into the contributions of each figure in formulating the psychomotor taxonomy, which is important for understanding how motor skills can be measured and evaluated objectively in the current educational context. Teachers as educators and other experts can use the views of the figures in this article as guidelines in conducting learning evaluations in the psychomotor field to measure students' skills.